Political Godmother : Nackey Scripps Loeb and the Newspaper That Shook the Republican Party - Heckman, Meg (Book collections on Project MUSE., 2020)
"A biography of Nackey Scripps Loeb, the longtime publisher of the "Manchester (NH) Union Leader," that traces connections between her influence and our current political moment"--